Meningkatkan Hasil Belajar IPS melalui Penerapan Model Pembelajaran Kooperatif Tipe Teams Games Tournament Berbantuan Media Baamboozle - Arizkia Dwi Kamila; Mahmud Yunus; MIra Amelia Amri (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study was motivated by the low social studies achievement of fourth-grade elementary school students. The study aimed to improve student achievement through the implementation of the Teams Games Tournament learning model supported by the Baamboozle platform. This study employed the Classroom Action Research (CAR) method, conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. Data collection techniques were conducted through tests, observations, and documentation. The results indicate that the implementation of the Teams Games Tournament learning model supported by the Baamboozle platform can improve student learning outcomes. This is evidenced by an increase in student learning achievement from 71% in Cycle I to 84% in Cycle II. In addition, student activity during the learning process also increased, with students becoming more active, enthusiastic, and cooperative in discussions and tournaments. Thus, the Teams Games Tournament learning model supported by Baamboozle is effective in improving elementary school students’ social studies learning outcomes.